EKOLOGI DAERAH URBAN (PERKOTAAN) DAN GANGGUAN KESEHATAN JIWA) - Yunita Satya Pratiwi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2016)
City is a form of ecological systems are complex, dynamic, and dominated by humans. In this case, the city is considered as an ecosystem that is an artificial environment, the result of a process of interaction between man and man and between man and his environment. The growth of urban population in the world, especially in Indonesia is relatively high, will continue with a high acceleration. In the period 2005-2030 the number of the world's urban population is expected to increase 56%, Asia up 71%, and up 74% in Indonesia. In 2005 the Indonesian population living in urban areas reached more than 107.9 million people, where 20% of whom were in Greater Jabodetabek (UNDP and ADB, 2006). Rate of population growth is not accompanied by the growth of the region, will result in overcrowding. This causes an imbalance of urban ecosystems. In addition to the emergence of poverty, unemployment, crime, uneven development, urbanization, suspected to be the cause of many community members are prone to stress and anxiety that lead to mental disorders. It is supported by a number of research results that show the prevalence trend of population show symptoms of mental health disorders in relatively more in urban than in rural areas. Keywords: Urban ecology, Ecosystems and Mental disorder